The Historical Value of Huangdi Neijing and the Tracing of Its Patriotic Genes - Shi, Chaoqiong; Yu, Juan; Zhuang, Yiyang; Bi, Shangqing; Yang, Weiping; Chang, Qingqing; Feng, Xiuping; Zhang, Jiaming (Journal of Social Science and Humanities, 2025)
Throughout the millennia-long historical transmission of Huangdi Neijing (The Yellow Emperor’s Inner Canon), its stratified developmental history embodies profound historical value. The cultural subjectivity manifested through national wisdom and the tracing of its spirit of undertaking social responsibility constitute a deep-seated patriotic significance, which is worthy of our study and inheritance.